THE CHANGES OF THE MEETING INDUSTRY IN KRAKOW IN THE CONTEXT OF THE GLOBAL CRISIS - KRZYSZTOF BORODAKO; JADWIGA BERBEKA; KATARZYNA KLIMEK; AGATA NIEMCZYK PhD, Senior Researcher, Tourism Department, Krakow Uni; RENATA SEWERYN (Tourism & Management Studies)
The main purpose of the paper is to identify changes in the meeting industry in Krakow. One of the reasons for the changes was the global crisis. An attempt to prove the thesis has been undertaken. Research on the meeting industry in Krakow was conducted on the basis of a questionnaire addressed to operators of facilities that can organise business events of this type. The respondents were asked about quantitative data connected with the business tourist traffic, but the questions also concerned opinions connected with the development of this market segment. At the beginning of the study, a review of literature devoted to the issues of shaping the demand for business tourism, with special consideration of the impact of the economic crisis on it, was conducted. In the empirical part, research results conducted in Krakow in 2008 -2010 were presented. They illustrate the number of MICE type events in the city, their structure and seasonality. The sectors of the parties ordering MICE type events in the city were listed. The number of participants of the events was analysed, divided into national and international participants. The results of the research allowed for the ascertainment that the economic crisis affected the changes of the level, and above all, the structure of MICE type events organised in the city, which was visible in 2010, therefore with some time delay. Fewer events were organised in the city, but they were more numerous in terms of the number of participants. This has an economic and psychological justification, and it can be deduced that the aforementioned changes were induced by the economic crisis.